PENGARUH BRAND IDENTITY DAN ONLINE COSTUMER REVIEW TERHADAP KEPUTUSAN BERLANGGANAN LAYANAN MUSIK STREAMING SPOTIFY PREMIUM DI KOTA BANJARMASIN - Rangga Novansyah; Muhammad Hasanur Arifin; Noor Hidayati; Taharuddin (Smart Business Journal (SBJ), 2025)
The rapid advancement of digital technology has dramatically transformed the way people consume music, moving from traditional physical media to modern streaming services such as Spotify. This research carefully investigates the effect of Brand Identity and Online Customer Reviews on the decision to subscribe to Spotify Premium in Banjarmasin City, both individually and collectively. A quantitative research method with a causal explanatory design was applied. The population consists of active Spotify Premium users in Banjarmasin, with 100 respondents carefully selected through purposive sampling techniques. Data were collected using structured online questionnaires and analyzed via Multiple Linear Regression in SPSS version 27.0. Findings reveal that Brand Identity positively and significantly impacts subscription decisions. Likewise, Online Customer Reviews also have a significant positive effect. Together, both factors considerably influence the choice to subscribe. The coefficient of determination (R²) is 0.570, showing that 57% of subscription decision variance is explained by Brand Identity and Online Customer Reviews, while 43% is affected by other important factors outside the scope of this particular study. It is recommended that Spotify continue strengthening its strong visual identity and distinctive features like “Spotify Wrapped” while actively leveraging positive customer feedback to consistently support long-term user growth.